Density dynamics: a holistic understanding of high density environments - Abraham, Jose P. (Kansas State University, 2014)
Today, achieving higher residential densities is an integral part of most discussions on concepts such as sustainability, placemaking, smart growth and new urbanism. It is argued that high density environments can potentially improve quality of life through a range of social benefits. In attempting to achieve these benefits, often times, developments that provide more than a certain number of dwelling units are considered desirable and successful high-density developments. However, understanding high residential density merely in terms of an increase in the number of dwelling units over an area of development might not help realize meaningful social benefits; in fact it could result in problems such as parking constraints, increased vehicular traffic, crowding, and eventually abandonment. This implies a dilemma of understanding high density environments holistically. Using literature review and design exploration as two key research methods, this project aims at resolving this dilemma by presenting a holistic understanding of desirable high-density environments. The research works on the idea that high densities are a matter of design and performance. Through synthesis of literature review and explorative design findings, this research focuses on the qualitative aspects of high density environments that make them meaningful and desirable. Through synthesis of literature review and design findings, the research finds that desirable high density environments should (a) Be Physically Compact; (b) Support Urbanity; and (c) Offer Livability and Sense of Place. These three qualitative aspects of high density environments are critical in determining how well such environments perform. The research further proposes eight meaningful goals and seventeen specific guidelines to achieve aforementioned three qualities that influence the performance of high density developments. In addition to these principles and guidelines, opportunities and challenges posed by explorative design exercises also allows identifying certain supplementary guidelines necessary to strengthen the framework. Together, these findings result in a theoretical framework that may be used as an effective design and evaluation tool in considering high density environments. This framework is named “Density Dynamics” to signify various morphological and socio-economic dynamics involved in a holistic understanding of high density environments.
Keywords: Urban design, Urban Planning, Redevelopment projects, Urban density, Residential density, High density; Architecture (0729); Land Use Planning (0536); Urban Planning (0999)